Implementasi Kebijakan Pengelolaan Pasar Rakyat Pada Pasar Sukodono Kabupaten Sidoarjo - Yulio Astria Yudha Firnanda; Lukman Arif (Universitas Batanghari Jambi, 2022)
The market is one of the places used to meet the needs of people's lives. Currently, it is necessary to realize that traditional markets are not the only trading centers. The increasing number of other trading centers such as modern markets, both in the form of minimarkets, hypermarts and malls which in turn can make traditional markets must be able to survive in the competition so as not to be crushed by the flow of modernization. However, in practice, the people's market still faces problems. This study aims to analyze and describe the implementation of the People's Market Management Policy at the Sukodono Market, Sidoarjo Regency. The type of research used by the author in this study is descriptive qualitative. The data sources of this research are primary data sources which are obtained from research informants and secondary data sources obtained from books, journals, and documents related to this research. Then the data collection techniques used in this study were interviews with purposive sampling method, direct observation (non-participants), and documentation with related data. In addition, the data analysis technique used is using interactive data analysis. The results of this study show that the implementation of the people's market management policy in Sukodono Market has been implemented but has not been optimal as a whole. This can be seen in the efficient, accountable, public interest, environmentally friendly, social responsibility and mutual cooperation focus that have been implemented well. However, the effective and productive focus has not been implemented optimally.